ChemInform Abstract: Synthesis of Pyrido[2, 1‐a]isoquinolin‐4‐ones and Oxazino[2, 3‐a]isoquinolin‐4‐ones: New Inhibitors of Mitochondrial Respiratory Chain. Issue 15 (15th April 2014) - Moreno, Laura; Cabedo, Nuria; Boulange, Agathe; Parraga, Javier; Galan, Abraham; Leleu, Stephane; Sanz, Maria‐Jesus; Cortes, Diego; Franck, Xavier
Abstract Most of the new compounds are able to inhibit mitochondrial respiratory chain.